2018
DOI: 10.1371/journal.pcbi.1005953
|View full text |Cite
|
Sign up to set email alerts
|

SozRank: A new approach for localizing the epileptic seizure onset zone

Abstract: Epilepsy is one of the most common neurological disorders affecting about 1% of the world population. For patients with focal seizures that cannot be treated with antiepileptic drugs, the common treatment is a surgical procedure for removal of the seizure onset zone (SOZ). In this work we introduce an algorithm for automatic localization of the seizure onset zone (SOZ) in epileptic patients based on electrocorticography (ECoG) recordings. The proposed algorithm builds upon the hypothesis that the abnormal exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 41 publications
(57 reference statements)
1
32
0
Order By: Relevance
“…By downsampling the required model order can be reduced, while a longer history can be taken into account (Murin et al. 2016 , 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…By downsampling the required model order can be reduced, while a longer history can be taken into account (Murin et al. 2016 , 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…40 Our findings contribute to a growing body of recent work aiming to identify epileptogenic networks and predict outcomes based on node-level measures. 15,17,[41][42][43][44][45] While most of this prior work uses ictal or preictal recordings, we focus on deriving information from the earliest available interictal data. Moreover, unlike the majority of previous studies, we apply quantitative imaging methods and semi-automated segmentation techniques to delineate the resection cavity, rather than utilizing subjective clinical identification of electrodes that are resected or part of the seizure onset zone.…”
Section: High Interictal Connectivity Within the Resection Zone Is Asmentioning
confidence: 99%
“…In the case that all the weights are equal, net-flow ranks according to the degree centrality of the nodes. The work [15] also proposed a ranking method based on the PageRank algorithm [16]. For the analysis of financial data, we observed that the method based on PageRank yields results similar to the netflow approach.…”
Section: Problem Formulationmentioning
confidence: 92%